Slawatan Jawa: Ekspresi Etnopuitika Budaya Jawa - Umilia Rokhani; Galih Pengestu Jati; Akbar Bagaskara (LP2M ISBI Bandung, 2026)
Slawatan, a hybrid culture rooted in Arab culture, developed in Java by adapting to the local culture. This study presents a case study Javanese slawatan tradition in the Langen Ambiya Group, Sleman Regency. Its existence is closely related to oral traditions and religious rituals expressed as distinctive Javanese performances and related to local knowledge. This study uses a structural method to examine the correlation between variations in form and meaning in slawatan lyrics. The results show that structurally, Javanese slawatan songs are developed through variations in the use of Arabic, Javanese, and a mixture of both languages. The performances also show similarities with Javanese palantun langgam, which reinforces the local aesthetic character of this tradition. These findings confirm that Javanese slawatan not only functions as a medium for religious preaching and entertainment, but also as a means of negotiating a dynamic cultural identity amid social change in society.